Contrasting effects of exogenous and endogenous attention on size perception. (25th August 2021) - Han, Yifei; Tan, Zhihao; Zhuang, Huang; Qian, Jiehui
Abstract : Although neuroimaging studies have shown that exogenous and endogenous attention are dissociable, only a few behavioural studies have explored their differential effects on visual sensitivity, and none have directly focused on visual appearance. Here, we show that exogenous and endogenous attention produces contrasting effects on apparent size. Participants performed a spatial pre‐cueing comparative judgement task that had been frequently used to test the attentional effects on visual perception. The results showed that a smaller stimulus within the focus of exogenous attention was perceived to be equal in size as a larger unattended stimulus, whereas a larger stimulus within the focus of endogenous attention was perceived to be equal in size as a smaller unattended stimulus. In other words, exogenous attention increased the perceived size while endogenous attention decreased the perceived size. The contrasting effects may be attributed to the mechanism that exogenous attention favours parvocellular processing for which more neurons with smaller receptive fields (RFs) are activated for a given size, whereas endogenous attention favours magnocellular processing for which fewer neurons with larger RFs are activated. This finding shows that exogenous and endogenous attention acts differentially on size perception, and provides supportive evidence for the distinct mechanisms underlying the two types of attentional processing.